Extraction and Purification of Amylase from Bacillus Cereus Isolated from Soil - Ashraf Abd Alhussien; Rahman Laibi Chelab (University of Thi-Qar Journal of Science, 2025)
The goal of this study was to isolate bacteria that produce amylase from soil samples that were taken from Al-Chibayish Marsh, which is located south of the Thi-Qar Governorate in Iraq. Using plating and repeated dilution techniques, isolation was accomplished. From the gathered soil samples, eighteen bacteria were identified. Using the starch agar plate method, all isolates were tested for starch activity. Of the 18 bacterial isolates, only 6 were able to make amylase; the two isolates with the highest production efficiency were chosen. Bacillus cereus was determined to be the source of the two isolates (the putative strain) by molecular, biochemical, and microscopic tests. The 48-hour incubation time, pH of 5, temperature of 37°C, starch concentration of 2%, and the use of dextrose as a carbon source and meat extract as a nitrogen source produced the highest levels of enzyme activity. The results of the present study showed that B. cereus isolates were capable of producing amylase enzyme, and the results indicated that nutrients and medium characteristics played a pivotal role in amylase enzyme production.